Glycemic responses to carbohydrate sources in the horse. - Gunkel, Christina Denise (Kansas State University, 2011)
There is increasing interest in the use of point-of-care glucometers to monitor glucose concentrations in horses with metabolic disorders. The first study reported herein compared equine glucose concentrations obtained by a handheld glucometer using whole blood or plasma, a YSI 2300 bench top glucose analyzer using whole blood or plasma, and a SEVEN continuous glucose monitoring (CGM) device that measured glucose in interstitial fluid to readings obtained by a standard laboratory glucose analyzer utilizing plasma. In addition, glucose concentrations obtained by the CGM were compared to those obtained by the handheld glucometer using whole blood or plasma. Post-prandial increases and decreases in glucose concentrations were detected utilizing all glucometers tested. When glucose measurements obtained with the CGM in interstitial fluid were compared to glucose measured using the handheld glucometer in plasma or whole blood, glucose measurements from plasma had better reproducibility. Although the CGM could be a useful instrument for collecting nearly continuous data for the researcher and clinician, there are technical difficulties related to the CGM that must first be overcome. The second study was designed to compare the effects of consuming a twice-daily meal of sweet feed (SF) to ad libitum access to a molasses-based block (BL) supplement on patterns of interstitial glucose concentrations in horses. A novelty effect of the BL was observed, in which horses consumed increased quantities in the first 12 h. Treatments had no effect on intake of forage in this study. The range and means of glucose values were similar between treatments, and significant glucose responses to treatments had lag times that were indirectly similar, even though molasses intake was greater for horses on BL. Variability between horses was noted in quantity of BL consumed as well as timing and magnitude of glucose responses. Based on the results of this experiment, there does not appear to be a clear advantage to either treatment, SF or BL, in attenuating post-prandial glucose increases or in minimizing glucose fluctuations in the horse.
Keywords: Equine; Continuous glucose monitor; Glucometer; Glycemic response; Molasses-based blocks; Sweet feed; Animal Sciences (0475)